Engineered Aedes aegypti JAK/STAT Pathway-Mediated Immunity to Dengue Virus. - Natapong Jupatanakul; Shuzhen Sim; Yesseinia I Angleró-Rodríguez; Jayme Souza-Neto; Suchismita Das; Kristin E Poti; Shannan L Rossi; Nicholas Bergren; Nikos Vasilakis; George Dimopoulos (Public Library of Science (PLoS), 2017)
We have developed genetically modified Ae. aegypti mosquitoes that activate the conserved antiviral JAK/STAT pathway in the fat body tissue, by overexpressing either the receptor Dome or the Janus kinase Hop by the blood feeding-induced vitellogenin (Vg) promoter. Transgene expression inhibits infection with several dengue virus (DENV) serotypes in the midgut as well as systemically and in the salivary glands. The impact of the transgenes Dome and Hop on mosquito longevity was minimal, but it resulted in a compromised fecundity when compared to wild-type mosquitoes. Overexpression of Dome and Hop resulted in profound transcriptome regulation in the fat body tissue as well as the midgut tissue, pinpointing several expression signatures that reflect mechanisms of DENV restriction. Our transcriptome studies and reverse genetic analyses suggested that enrichment of DENV restriction factor and depletion of DENV host factor transcripts likely accounts for the DENV inhibition, and they allowed us to identify novel factors that modulate infection. Interestingly, the fat body-specific activation of the JAK/STAT pathway did not result in any enhanced resistance to Zika virus (ZIKV) or chikungunya virus (CHIKV) infection, thereby indicating a possible specialization of the pathway's antiviral role.